Factors Related to Active Learning Management of Nursing Students - Thoin, Pasinee; Khoyun, Siriorn; Srioad, Phattnee; Kitkhaundee, Benjawan (Journal of The Royal Thai Army Nurses, 2025)
This descriptive research aimed to study nursing students’ attitudes toward active learning and to examine the relationship between various factors, including the classroom environment, teaching media, teaching activities, and instructors. The sample consisted of 218 nursing students from Boromarajonani College of Nursing, ranging from the 1st to 4th year in the academic year 2024. The research instrument was a questionnaire assessing nursing students’ attitudes toward active learning and the factors related to these attitudes. The content validity of the questionnaire, resulting in a content consistency index of 0.67 to 1. The reliability of the questionnaire was determined using Cronbach’s alpha coefficient, yielding a reliability score of 0.97. Data were analyzed using descriptive statistics, including frequency, percentage, mean, standard deviation, and Pearson’s product-moment correlation coefficient. The research findings indicated that: 1) Nursing students had a high level of positive attitudes towards active learning (Mean = 3.72, S.D. = 0.61). 2) Factors such as teaching activities, instructors, teaching media, and classroom environment had statistically significant positive relationships with students’ attitudes toward active learning, with correlation coefficients (r= 0.63., 0.61, 0.53 and 0.43, respectively), with a p-value of <0.001.